Interaction of cytochrome P450s with environmental risk factors increases their expression and risk to head and neck cancer. (11th June 2022) - Katiyar, Tridiv; Yadav, Vinay; Maurya, Shailendra S.; Hasan, Feza; Singh, Arvind P.; Yadav, Sanjay; Singh, Sudhir; Hadi, Rahat; Bhatt, Madan Lal B.; Parmar, Devendra
Abstract: To investigate the role of interaction of tobacco metabolizing polymorphic cytochrome P450s (CYPs) and glutathione S‐transferase M1 (GSTM1) with environmental risk factors in modifying the susceptibility to head and neck squamous cell carcinoma (HNSCC), a case–control study with 1250 proven cases of HNSCC and equal number of healthy controls was planned. A small but significant increase in the risk to HNSCC (1–2 fold) in the cases with variant genotypes of CYPs ( 1A1 or 1B1 or 2E1) increased several folds (up to 13 fold) in regular tobacco or alcohol users. This several fold increase in risk could be due to more than multiplicative interaction observed between the risk genotypes of CYPs and tobacco or alcohol. A synergistic effect was also observed between tobacco as well as alcohol users among cases with risk genotypes of CYPs and GSTM1 that resulted in a further increase in risk (up to 29 fold) to HNSCC. Interestingly, the increase in the risk in tobacco users among cases with variant genotypes of CYPs or a combination of CYPs & GSTM1 (−) was associated with a higher mRNA expression of CYPs when compared to nontobacco users in controls with wild type of genotypes of CYPs & GSTM1 . The data suggest that the interaction of genetic and environmental risk factors leads to increased expression of CYPs which may increase the levels of tobacco‐derived carcinogens thereby modifying the risk to HNSCC.